2017
DOI: 10.4236/jct.2017.86048
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of Neuroblastoma Cell Growth by Difluoromethylornithine (DFMO) and Bortezomib through Suppression of LIN28 and MYCN

Abstract: Neuroblastoma (NB) is the most common childhood cancer arising from the nervous system. Many high-risk neuroblastoma (HRNB) patients develop relapse after initial response to induction treatment and overall long term survival remains poor (less than 60%), emphasizing the need for new therapeutic approaches and more effective treatments. Combination therapies present a favorable approach to improve efficacy, decrease toxicity, and reduce development of drug resistance. Difluoromethylornithine (DFMO) has shown p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 45 publications
0
2
0
Order By: Relevance
“…Particularly the hypusination of eukaryotic translation initiation factor 5A (5IF5A) can influence MYCN trhough the Lin28B/let7 axis. In neuroblastoma, DFMO has been found to reduce Lin28B protein and increase Let-7 miRNA levels 48 , 49 . In addition to this polyamines may influence oncogenic pathways such as mTORC1 which plays a key role in supporting protein synthesis.…”
Section: Discussionmentioning
confidence: 99%
“…Particularly the hypusination of eukaryotic translation initiation factor 5A (5IF5A) can influence MYCN trhough the Lin28B/let7 axis. In neuroblastoma, DFMO has been found to reduce Lin28B protein and increase Let-7 miRNA levels 48 , 49 . In addition to this polyamines may influence oncogenic pathways such as mTORC1 which plays a key role in supporting protein synthesis.…”
Section: Discussionmentioning
confidence: 99%
“…The same study has also shown that the sensitivity to treatment with DFMO correlates with overexpression of LIN28B (BE(2)‐C>SMS‐KCNR>CHLA90) 208 . Bortezomib has also been found to inhibit LIN28B expression, and the combination of bortezomib and DFMO leads to more significant inhibition of LIN28B expression in NB cells than treatment with either agent alone 209 . A derivative of vitamin K3 (VK3‐OH) has also been found to suppress LIN28B at the protein as well as mRNA levels in MYCN‐driven NB cells 210 .…”
Section: Preclinical Studies Of Targeted Nb Therapymentioning
confidence: 87%